Usability of Some Landscape Plants in Biomonitoring Technique: an Anaysis With Special Regard to Heavy Metals - IŞINKARALAR, Kaan; IŞINKARALAR, Öznur; ŞEVİK, Hakan (Kent Akademisi, 2022)
As a result of the widespread industrial activities in today's cities and the increase in the urban population and building density, the pollution values in the urban geography are increasing. The accumulation of environmental pollutants is one of the most important problems to be considered in the construction of cities. Heavy metal pollution from various activities in urban areas is one of the riskiest environmental problems. Heavy metals are concentrated due to human activities and it is necessary to monitor and determine their accumulation levels. Detection and reduction studies of heavy metal levels in regions and areas with population density are of critical importance, as accumulation above a certain dose can cause vital problems. Studies on the accumulation of heavy metals are affected by parameters of quite different sizes, and determination of the level and identification of the source is quite complex. However, due to the high accumulation of pollutants in some landscape areas due to the effect of their type, it reveals the course of pollutants in these regions. This study aimed to determine the concentrations of Copper (Cu) and Iron (Fe) in leaves, bark and wood in various landscape species by biomonitoring heavy metals. By comparing the Cu and Fe concentrations, the heavy metal holding capacities of the species used varied significantly in plant species and in different organs of the same plant. As a result of the study, it has been determined that Schinus molle L. can be preferred in urban areas and can be used as a biomonitor in Cu and Fe accumulation.
Keywords: Environmental Engineering; ağır metal; biyoizleme; hava kirliliği; kentsel yeşil alan; Air pollution; Biomonitoring; heavy metals; Urban green; Çevre Mühendisliği; 15. Life on land; 6. Clean water; 12. Responsible consumption; 13. Climate action; 11. Sustainability